Upgrading Human Resource Management for Branding Company - Ega Janurdi (Return : Study of Management, Economic and Bussines, 2023)
Human resources largely determine the process of successful performance of an organization. Human resource development, aims to facilitate the realization of organizational goals, because the quality of human resources is considered capable in carrying out their duties and functions as employees in a company. Therefore, it is necessary to increase even better human resources in the company's brand. The method in this study is the library research method, with a qualitative approach. The result of this study is that through better and more optimal HR planning and implementation, the right men in the right place. Efforts that can be made by a company in improving the quality of human resources are by conducting employee training and development and rewards that stimulate someone to be able to increase knowledge, dedication and development of human resources in a company.